Improving the blood flow signal in coronary bypass by detection of eventual distortions - Torres Guzmán, D.; Carbajal Fernández, C. S. (Revista Mexicana de Ingenieria Biomedica, 2015)
This paper aims to implement a method for signals processing in biomedical applications based on Doppler ultrasound techniques. The method is aimed to obtain a better representation of the blood flow signal, and it is based on the detection and exclusion of signal cycles detected as affected by eventual noise. This allows, in robust and reliable way, to estimate parameters and extract useful clinical information, in order to make accurate diagnoses on the functionality of the scanned object. The results of applying the method to two blood flow signals in coronary implants are presented, and it is observed that the estimation of the clinical indices improve when affected cycles are excluded of the signal analysis.